Improved spectral sensitivity by combining periodic shadowing and high dynamic range imaging. Issue 2 (7th February 2016) - Kristensson, Elias; Ehn, Andreas
ABSTRACT: Most emission spectra are characterized by lines of various intensities, a feature making them difficult to probe in their entirety – the limited dynamic range of the detector prohibits the simultaneous observation of both weak and intense spectral features. A further known complication in spectroscopy concerns the generation and detection of stray light, which is an undesired contribution of light, often associated with unavoidable imperfections in the spectrometer. Stray light leads to an offset that often exceeds the intensity of weak lines, especially those that were barely detectable in the absence of stray light. This problem is well-known in, for example, laser-induced Raman spectroscopic measurements. In this paper, we describe a methodology to solve both the stray light problem and that associated with the limited dynamic range of the detector. The method is based on combining the high dynamic range imaging concept commonly employed in digital photography with the periodic shadowing technique, where the former is used to boost the dynamics and the latter to suppress stray light. The capabilities of the approach, which is suitable for investigation of temporally stable sources, are demonstrated and the results are compared with measurements performed with both conventional equipment and the periodic shadowing technique.